Assessing physician knowledge regarding indications for a primary prevention implantable defibrillator and potential barriers for referral. (14th September 2017) - Bernier, Rochelle; Raj, Satish R.; Tran, Dat; Reyes, Lucy; Sauve, Michel; Sumner, Glen L.; Exner, Derek V.; Sandhu, Roopinder K.
Abstract: Background: Although there is clear evidence to demonstrate that primary prevention implantable defibrillators (ICDs) reduce mortality in high‐risk patients, ICDs are underutilized. Limited data exist assessing referring physicians' knowledge about guideline indications and attitudes towards ICDs, which may influence decision for referral. Methods and results: The Arrhythmia Working Group from the Alberta Cardiovascular and Stroke Strategic Clinical Network developed a web‐based survey consisting of case scenarios regarding primary prevention ICD indications and a list of barriers for referral to aid in the design of a complex device care pathway. We invited referring physicians to participate in the survey including internists and cardiologists and cardiology residents. The survey was completed by 109 of 799 (response rate = 14%) of physicians. Of those, 55% were internists, 32% cardiologists, and 13% cardiology residents. The majority of physicians were male (62%), practicing in a university hospital (66%). Overall, complete guideline‐concordant answers were provided by 34% of physicians. In multivariable analysis, predictors of complete guideline concordance were being a cardiologist (odd ratio [OR] 5.9, confidence interval [CI] 2.1–16.4, P = 0.001) and cardiology resident (OR 6.7, CI 1.7–27.3, P = 0.007). The most common barrier for referral for internists was lack of confidence in knowledge of guideline recommendations; while cardiologists reported concerns about cost‐effectiveness and cardiology residents were most concerned with inappropriate shocks. Conclusion: Knowledge regarding indications for primary prevention ICD is limited and varies significantly among referring physicians. The barriers for referral differ among physician groups and addressing these identified barriers may help to improve appropriate ICD utilization.